Three-Dimensional Analytical Model for the Dispersion of Air Pollutants Emitted from Elevated Point Source with Mesoscale Wind - v nirmaladevi, P.; K, Lakshminarayanachari; C, Pandurangappa (International Journal of Engineering and Technology, 2018)
A three-dimensional analytical method is evolved to analyze the distribution of air impurities released from raised point of reference in the civic zone in the existence of mesoscale wind along with huge air current. The huge air current and eddy diffusivities are taken as constants. The purpose of developing a model is for better understanding of the physical, chemical and dynamical properties of air pollution and meteorology. The analytical model is solved using the Fourier transform technique, variable separable method and series solution. In an urban area, mesoscale wind prevents the distribution of air impurities in the aerosphere. As a result of this there will be rise in aggregation of impurities in the aerosphere. The aggregation of air impurities is less for the point source which is at the origin in the existence of mesoscale wind as indicated by the research investigation.Â